A case of venous malformation of maxillary alveolar ridge managed with polydocanal injections and Er:Yag laser: a case report - Kumar, Andrews N.; Mishra, Chandan; Mehta, Sandeep; Preet, Emaan; Dua, Gaurav (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
We present a case involving a venous malformation on the left maxillary alveolar ridge in an adult, which was successfully managed using a combination approach of Polidocanol injection and soft tissue Er:Yag laser. Vascular malformations (VM) encompass a group of anomalies affecting capillary, venous, lymphatic, and arterial systems, characterized by structural irregularities in blood vessels without endothelial proliferation. These anomalies are typically present at birth, can manifest in childhood or adolescence, and persist throughout life. In this specific case, a 65-year-old female patient presented with a bluish-black growth on her left maxillary alveolar ridge, later diagnosed as a VM. The treatment regimen involved Polidocanol injections, Quilting sutures, and ultimately excision with a 980-nm soft tissue Er:Yag laser. This combined approach, employing sclerotherapy, Quilt suturing, and Er:Yag laser with appropriate precautions, proved effective in managing the VM of the maxillary ridge, underscoring the significance of utilizing pharmacologic and surgical techniques for optimal management of vascular lesions.